Enhanced power generation using controlled inoculum from palm oil mill effluent fed microbial fuel cell - Baranitharan, E.; Khan, M.R.; Yousuf, A.; Teo, W.F.A.; Tan, G.Y.A.; Cheng, C.K. (Elsevier Sci. Ltd., 2015)
Enhancing the anode performance is a critical step for improving the power output of MFCs. This study deals with the dual chamber MFCs to increase the power generation using the controlled inoculum in Palm oil mill effluent (POME). Controlled inoculum (CI) was made using the predominant microorganisms such as Pseudomonas aeruginosa, Azospira oryzae, Acetobacter peroxydans and Solimonas variicoloris isolated from palm oil anaerobic sludge (AS) as well as from biofilm of MFC anode operated with AS and identified using BIOLOG gene III analysis, PCR, DGGE and sequencing. Biofilm formation on electrode was investigated by Fourier Transform Infrared spectroscopy (FTIR) and Thermogravimetric analayis (TGA). The MFC operated with Polyacrylonitrile carbon felt (PACF) anode and CI reached the maximum power density of 107.35 mW/m(2), which was two times higher as compared to MFC operated with usual anaerobic sludge as inoculum. The maximum coulombic efficiency (CE) of 74% was achieved from the MFC with CI, which was 50% higher than the CE with anaerobic sludge. But, it showed lower COD removal efficiency of about 32%, which might be due to the absence of required fermentative microorganisms in CI to utilize POME. The electrochemical activities have been investigated by electrochemical impedance spectroscopy (EIS). EIS and the simulated results showed the significant reduction of charge transfer resistance (R-ct) by similar to 40% during the operation of the cell with CI. EIS results provided evidence that there was a substantial improvement in electron transfer between the microorganisms and the anode with CI. These results demonstrate that the power output of MFCs can be increased significantly using CI. (C) 2014 Elsevier Ltd. All rights reserved.